Assessing Legal Measures for Addressing Personal Data Misuse in Commercial Settings: A Critical Analysis: Tinjauan Hukum terhadap Mekanisme Penegakan Hukum atas Pelanggaran Penyalahgunaan Data Pribadi di Pasar - Anissa, Salsabila; Multazam, Mochammad Tanzil (Universitas Muhammadiyah Sidoarjo, 2024)
This study delves into the legal framework governing personal data protection in Indonesia, focusing on mechanisms to safeguard information and penalize offenders. Employing a normative juridical and conceptual approach, statutory and conceptual analyses were conducted to identify pertinent legal provisions. Examination of primary and secondary legal sources was undertaken to scrutinize the enforcement of laws in cases of personal data abuse. Marketplaces, serving as pivotal platforms for transactions and data sharing, entail inherent risks to privacy and security. Users routinely disclose personal details, necessitating robust safeguards against misuse. The findings underscore the imperative of effective legal mechanisms to mitigate personal data abuse, ensuring enhanced privacy and security within Indonesian marketplaces. Highlights : The study employs a normative juridical and conceptual approach to analyze the legal framework governing personal data protection in Indonesia. Marketplaces serve as crucial platforms for transactions and data sharing, necessitating effective mechanisms to safeguard personal information. Examination of primary and secondary legal sources reveals the need for robust enforcement measures to deter and penalize perpetrators of personal data abuse. Keywords: Personal data protection, Indonesia, Marketplaces, Legal mechanisms, Data abuse